Integrated Vlog Media Development of Ethno-STEM to Equip Concervation Character and Chemistry Literacy - Elva Laila; Sudarmin Sudarmin; Agung Tri Prasetya (International Conference on Science, Education, and Technology, 2022)
Abstrak. Hydrocarbon material is a material that examines abstract concepts related to atoms and structures. However, Generation Z has characteristics that rely heavily on digital technology. Characteristics of materials and students who are different, of course, will hinder achieving the objectives of learning hydrocarbons. Chemistry learning will be effective if hydrocarbon material is integrated through the development of vlog media content that raises local wisdom or ethno-STEM (science, technology, engineering, and mathematics). So, will provide in-depth and comprehensive understanding of students into scientific knowledge. The research aims to produce an ethno-STEM integrated vlog media and its effect on the provision of conservation characters and chemistry literacy of students. The development of ethno-STEM integrated vlog media in research uses the 4D method, namely definition, design, development, and dissemination aimed at class XI science students who are studying hydrocarbon material at SMA Negeri 3 Batam. The data was obtained through observation and structured interviews with 1 chemistry teacher and 17 students. The results of the validity of the material (0,87), media (0,77), teacher practicality (0,79), student responses on the small-scale (0,79), large-scale (0,83). The vlog media (0,91), conservation character (0,63) and chemistry literacy correlation coefficient (0,54). The reliability of the question (0,58), discriminating power (0,22) and difficulty level of the item pre-test (0,76) and post test (0,93). So, it can be concluded that the vlog media developed is valid, practical, and effective as local wisdom content to equip conservation characters and chemistry literacy.